TRAINING AND DEVELOPMENT SHAPED STAFF ATTITUDE: EXPLAIN THE RELEVANCE OF TRAINING AND DEVELOPMENT IN CHANGING STAFF ATTITUDE IN THE ORGANIZATION - Iselema, Gbaranbiri (Top Educational Review Journal (TERJ), 2024)
This paper explored the importance of training and development for organizations, specifically its impact on staff attitude. The study identified types of training, including on-the-job training, classroom-based training, online training, simulation-based training, gamification, train-the-trainer, and others. The methods included lectures, case studies, experiential learning methods, and reflective learning method. It also examined the relevance of training and development in shaping staff attitudes, with a focus on how training can improve competence, motivation, and value. The study identified common challenges that organizations face in implementing effective training and development programs, including lack of funding, culture, and incentives. The paper concluded that training and development is an important tool for organizations to use to improve employee engagement and satisfaction. The paper further offered suggestions for overcoming these challenges, such as increasing investment in training, creating a culture of learning, and offering rewards for participation. By addressing these challenges and implementing the suggested solutions, organizations can improve the effectiveness of their training and development programs